Konsep 'Ibu Pertiwi' sebagai Landasan Inkulturasi Ekologi Integral Gereja Katolik di Indonesia - Thersiani Bheka; Intansakti Pius X (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This article responds to the challenge of contextualizing Laudato Si's teachings on integral ecology in the Indonesian Catholic Church. This study examines the concept of